Defining and Measuring Excellence Orientation as a Cultural Dimension - Kaur, Harsimar (My University, 2025)
This study introduces excellence orientation as a new cultural dimension and develops a scale to measure it. The development of the scale followed an iterative process that included an extensive literature review, expert validation, and face validation to ensure the content’s relevance and accuracy. The scale was designed to capture two aspects of excellence orientation: practices (what people actually do) and perceptions (how people perceive their society's focus on excellence). The data collected were analysed for Cronbach’s alpha reliability, inter-item correlations, and exploratory factor analysis (EFA) to test the scale’s construct validity. The results of the EFA indicated that both the practices and perceptions subscales loaded onto a single factor, confirming the unidimensional nature of the scale. To further validate the scale, a confirmatory factor analysis (CFA) was conducted with a new sample, and the fit indices confirmed that the model was a good fit to the data, establishing its validity and reliability. As a result of this process, a 5-item scale for measuring excellence orientation was developed, consisting of separate items for practices and perceptions, both rated on a 5-point Likert scale. The study’s findings confirm that the scale is a valid and reliable tool for assessing excellence orientation in different cultural contexts. This study contributes to the literature by introducing excellence orientation as a distinct cultural dimension, expanding our understanding of how cultural values can influence societal progress and behaviour. The scale developed in this study offers a valuable tool for researchers and practitioners to assess and understand cultural dynamics, particularly in organizational and societal settings.
Keywords: Excellence orientation; culture; cultural dimensions; scale development; exploratory factor analysis; confirmatory factor analysis